Dysregulation of Astrocytic Glutamine Transport in Acute Hyperammonemic Brain Edema - Zielińska, Magdalena; Albrecht, Jan; Popek, Mariusz (Frontiers in Neuroscience, 2022)
Acute liver failure (ALF) impairs ammonia clearance from blood, which gives rise to acute hyperammonemia and increased ammonia accumulation in the brain. Since in brain glutamine synthesis is the only route of ammonia detoxification, hyperammonemia is as a rule associated with increased brain glutamine content (glutaminosis) which correlates with and contributes along with ammonia itself to hyperammonemic brain edema-associated with ALF. This review focuses on the effects of hyperammonemia on the two glutamine carriers located in the astrocytic membrane: Slc38a3 (SN1, SNAT3) and Slc7a6 (y + LAT2). We emphasize the contribution of the dysfunction of either of the two carriers to glutaminosis- related aspects of brain edema: retention of osmotically obligated water (Slc38a3) and induction of oxidative/nitrosative stress (Slc7a6). The changes in glutamine transport link glutaminosis- evoked mitochondrial dysfunction to oxidative-nitrosative stress as formulated in the “Trojan Horse” hypothesis.